Nursing students' self‐determination: the influence on stigmatizing attitude within clinical placement settings. (28th January 2019) - Perlman, Dana; Taylor, Ellie; Moxham, Lorna; Patterson, Chris
Abstract: The training of future health professionals is a complex and dynamic endeavour, whereby students engage in a variety of experiences and learning activities. Skills developed through classes are applied and further developed within authentic settings, such as clinical placements. While there is a wealth of literature that has examined the influence of clinical placements, less inquiry has examined whether the personal traits and/or characteristics of students play a role in their professional learning and development. Specifically, a key trait that has been viewed as influencing the education and growth of people, yet has received little focus in the nursing literature, is self‐determination. Therefore, the purpose of this study was to examine whether students' self‐determination influences their level of professional learning, as measured by their stigmatizing attitudes, within a clinical placement. Participants were undergraduate nursing students classified as either high or low in their self‐determination and engaged in a compulsory 80‐hour mental health clinical placement. Data were collected using a battery of surveys to assess their self‐determination towards their work and stigmatizing attitude towards people with mental illness. Using a two‐group pre test and post test design, statistical analysis revealed a significant difference whereby students with high self‐determination towards work possessed less stigmatizing attitudes after completing their clinical placement. Results from this study provide empirical evidence that personality elements such as self‐determination and motivation towards work can play a role in the education of future professionals.